The In-vivo Safety and Efficacy Test of Antiaging Serum Containing Gold Nanoparticle Synthesized Using Sida rhombifolia Extract - Waluyo, Dyah Ayuwati; Sutriyo, Sutriyo Sutriyo; Vardhani, Afifah K.; Wardana, Mutia Sari (Jurnal Fitofarmaka Indonesia, 2024)
Advance glycation end products (AGEs) are the basic root cause of endogenous aging. AGEs causing fragmentations and crosslinked collagen which damaging the skin integrity and mechanical properties resulting in reduced skin elasticity. Gold nanoparticles (AuNP) has been synthetized using Sida rhombifolia (Sidaguri) extract. This study aimed to determine the efficacy of antiaging serum containing AuNP synthetized using Sidaguri extract. AuNP was produced by reducing HAuCl4 solution using Sidaguri extract. 10% of AuNP colloid was formulated into the serum. 19 woman applied patch containing serum and base placebo to perform irritation test followed by provocative test if there is any reddish reaction found. 16 women showed no signs of irritation and 3 women showed a reddish reaction, the provocative test showed no signs of irritation. Then efficacy test performed to 18 women by applying 1 drop of the serum at one side of the forearm and base placebo serum at the other side, after passing patch test. The antiaging serum had the ability to increase skin collagen (64.72 ± 27.11%) and skin elasticity (64.11 ± 11.67%) after 8 weeks of use, twice a day. There was a significant increase in skin collagen and elasticity index (P-value < 0.0001).